1989
DOI: 10.1021/bi00445a002
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli initiation factor 3 protein binding to 30S ribosomal subunits alters the accessibility of nucleotides within the conserved central region of 16S rRNA

Abstract: Translational initiation factor 3 (IF3) is an RNA helix destabilizing protein which interacts with strongly conserved sequences in 16S rRNA, one at the 3' terminus and one in the central domain. It was therefore of interest to identify particular residues whose exposure changes upon IF3 binding. Chemical and enzymatic probing of central domain nucleotides of 16S rRNA in 30S ribosomal subunits was carried out in the presence and absence of IF3. Bases were probed with dimethyl sulfate (DMS), at A(N-1), C(N-3), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 32 publications
3
32
0
Order By: Relevance
“…Having established that IF3 contains two separate ribosomal binding sites (one in each of its domains) and having just described their molecular facets, for a better understanding of how IF3 might work, we think it relevant to suggest a plausible orientation of this molecule on the 30S ribosomal subunits+ Thus, the sites of the 16S rRNA molecule that have been found to be relevant for the interaction with IF3 have been highlighted with different colors (Fig+ 6) in the recently released 3D model of the 30S ribosomal subunit based on electron-microscopy reconstructions (Mueller & Brimacombe, 1997)+ The main binding site of IF3 on the 30S subunit contains the bulged stem-loop 674-713 (helix 23) and the 783-799 stem-loop (helix 24)+ In fact, a G-to-A transition at position 791 (purple) increases tenfold the dissociation rate constant of the IF3-30S complex (Tapprich et al+, 1989) and modification of the 16S rRNA by the guanosine-specific reagent kethoxal inhibits IF3 binding (Pon & Gualerzi, 1974), whereas G-700, G-703 (yellow), and G-791 (purple) are specifically protected from reaction with this reagent by IF3 (Moazed et al+, 1995)+ Furthermore, two rRNA regions (both white), the main one (819-859, corresponding to helices 25 and 26) within the central domain and the minor one (1506-1529, corresponding to helix 45) in the 39-end region of the 16S, have been crosslinked to IF3 (Ehresmann et al+, 1986)+ In agreement with these data is the recent finding that an inversion of the sequence (G-A to A-G) at positions 1530/ 1531 (at the edge of helix 45) results in a tenfold decrease in the affinity of IF3 for the 30S subunit (Firpo et al+, 1996)+ Moreover, this model is consistent with the finding that all 16S rRNA sites, which become hypersensitive or hyperexposed in the presence of IF3 to chemical or enzymatic probes such as RNase V1 (red), DMS (green), and kethoxal (turquoise; Muralikrishna & Wickstrom, 1989;Moazed et al+, 1995), are found at the edge or outside the IF3 binding site, confirming the conformational nature of the change leading to the hypersensitivity+ If docking of IF3 to the ribosomal subunit is done with the assumption that the primary rRNA binding site of the C-domain is in contact with the main rRNA sites crosslinked to and/or affected by IF3, which are clustered in the central area of the subunit, the emerging picture is that of a molecule that is implanted through extensive RNA-protein interactions in the central part of the ribosomal particle and reaches the upper margin of the side lobe (platform) where its N-domain touches helix 45 (i+e+, the last 39 terminal helix of 16S rRNA)+ IF3 is known to act as a fidelity factor that determines the kinetic discrimination against spurious 30S initiation complexes by forcing the dissociation of the noncanonical codon-anticodon interactions at the ribosomal P-site (Gualerzi et al+, 1971;Risuleo et al+, 1976;Hartz et al+, 1989)+ Theoretically, IF3 could accomplish this function by a direct inspection of the codon-anticodon interaction and/or the anticodon stem-loop of initiator tRNA (Hartz et al+ 1990) or affecting the conformation of the 30S ribosomal subunits …”
Section: Docking If3 To Its Binding Site On the 30s Ribosomal Subunitsupporting
confidence: 73%
“…Having established that IF3 contains two separate ribosomal binding sites (one in each of its domains) and having just described their molecular facets, for a better understanding of how IF3 might work, we think it relevant to suggest a plausible orientation of this molecule on the 30S ribosomal subunits+ Thus, the sites of the 16S rRNA molecule that have been found to be relevant for the interaction with IF3 have been highlighted with different colors (Fig+ 6) in the recently released 3D model of the 30S ribosomal subunit based on electron-microscopy reconstructions (Mueller & Brimacombe, 1997)+ The main binding site of IF3 on the 30S subunit contains the bulged stem-loop 674-713 (helix 23) and the 783-799 stem-loop (helix 24)+ In fact, a G-to-A transition at position 791 (purple) increases tenfold the dissociation rate constant of the IF3-30S complex (Tapprich et al+, 1989) and modification of the 16S rRNA by the guanosine-specific reagent kethoxal inhibits IF3 binding (Pon & Gualerzi, 1974), whereas G-700, G-703 (yellow), and G-791 (purple) are specifically protected from reaction with this reagent by IF3 (Moazed et al+, 1995)+ Furthermore, two rRNA regions (both white), the main one (819-859, corresponding to helices 25 and 26) within the central domain and the minor one (1506-1529, corresponding to helix 45) in the 39-end region of the 16S, have been crosslinked to IF3 (Ehresmann et al+, 1986)+ In agreement with these data is the recent finding that an inversion of the sequence (G-A to A-G) at positions 1530/ 1531 (at the edge of helix 45) results in a tenfold decrease in the affinity of IF3 for the 30S subunit (Firpo et al+, 1996)+ Moreover, this model is consistent with the finding that all 16S rRNA sites, which become hypersensitive or hyperexposed in the presence of IF3 to chemical or enzymatic probes such as RNase V1 (red), DMS (green), and kethoxal (turquoise; Muralikrishna & Wickstrom, 1989;Moazed et al+, 1995), are found at the edge or outside the IF3 binding site, confirming the conformational nature of the change leading to the hypersensitivity+ If docking of IF3 to the ribosomal subunit is done with the assumption that the primary rRNA binding site of the C-domain is in contact with the main rRNA sites crosslinked to and/or affected by IF3, which are clustered in the central area of the subunit, the emerging picture is that of a molecule that is implanted through extensive RNA-protein interactions in the central part of the ribosomal particle and reaches the upper margin of the side lobe (platform) where its N-domain touches helix 45 (i+e+, the last 39 terminal helix of 16S rRNA)+ IF3 is known to act as a fidelity factor that determines the kinetic discrimination against spurious 30S initiation complexes by forcing the dissociation of the noncanonical codon-anticodon interactions at the ribosomal P-site (Gualerzi et al+, 1971;Risuleo et al+, 1976;Hartz et al+, 1989)+ Theoretically, IF3 could accomplish this function by a direct inspection of the codon-anticodon interaction and/or the anticodon stem-loop of initiator tRNA (Hartz et al+ 1990) or affecting the conformation of the 30S ribosomal subunits …”
Section: Docking If3 To Its Binding Site On the 30s Ribosomal Subunitsupporting
confidence: 73%
“…The 790 loop is known to be of functional importance+ Initiation factor IF-3 footprints are at positions G791 and U793 as well as at positions G700, U71 and G703 (Muralikrishna & Wickstrom, 1989;Moazed et al+, 1995)+ IF3 also was crosslinked to two sites in the vicinity of the 790 end loop at position A829 and G859 (Ehresmann et al+, 1986)+ A mutation G791C inhibits initiation complex formation by decreasing the association rate constant for formation of the IF3{30S subunit complex (Tapprich et al+, 1989)+ In addition, the mutation A792G or C affects subunit association implicating the 790 end loop in contacts with the 50S subunit (Santer et al+, 1990)+ tRNA footprints for tRNA situated in the P site are at positions A794 and C795 in the 790 loop and at G693 in the 700 region (Moazed & Noller, 1990)+ The proximity of the 700 and 790 end loops was shown before by chemical crosslinking between fragments 693-696 and 794 (or 799) using nitrogen mustard as the crosslinking reagent (Atmadja et al+, 1986)+ Position G693 was also crosslinked by a diazirine reagent that was attached to position 32 of the anticodon loop of tRNA Arg I when that tRNA was in the P-site and E-site (Doring et al+, 1994)+ These data indicate that the 790 loop must be closely involved in determining the functional status of the decoding region and that the region G693-G703 also participates in this+…”
Section: Discussionmentioning
confidence: 99%
“…The site chosen in the present experiment is U788 in the 790 loop of the 16S rRNA+ This region is present in all small subunit RNAs and is highly conserved in sequence+ It has been implicated in several important 30S functions including subunit association (Chapman & Noller, 1977;Herr et al+, 1979;Santer et al+, 1990), IF3 binding (Muralikrishna & Wickstrom, 1989;Moazed et al+, 1995;Tapprich & Hill, 1986;Tapprich et al+, 1989), and tRNA binding (Moazed & Noller, 1990)+ The physical location for the region in the subunit has been investigated by DNA hybridization electron microscopy and was proposed to be in the end of the 30S subunit platform structure (Oakes & Lake, 1990); however, there is a significant distance between the decoding region and the proposed site, and it has been difficult to reconcile the rRNA segment location with its function+ The crosslinks made by the site-specific psoralen (SSP) reagent in these experiments are with a number of RNA sites that must be in the central part of the 30S subunit and this indicates a location for the nucleotides U788/U789 in the central part of the subunit much closer to the decoding region than previously thought+…”
mentioning
confidence: 99%
“…The interaction between IF-3 (the prokaryotic homolog to eIF-3 (19)) with 16 S rRNA in the 30 S subunit has been studied by site directed mutagenesis, footprinting, and direct crosslinking (7)(8)(9)20). These techniques show the importance of the central domain for ribosomal binding of IF-3.…”
Section: Discussionmentioning
confidence: 99%